Caracterização de fungos presentes em solos sulfetados da Antártica e sua avaliação para estudos em processos de biolixiviação de metais - Bárbara Alves Porto (2020)
Antarctica stands out for its low temperatures and low availability of nutrients, intense solar radiation and strong winds in its different ecosystems. In Antarctica there are soils with different physical and chemical characteristics, which represent interesting micro-habitats that house micro-organisms. Among the Antarctic soils, sulfurates (known as yellow points) stand out, which are formed by outcrops of sulfides with an acid and oligotrophic character. Among the microorganisms present in Antarctica, fungi stand out for their high adaptive capacity, tolerating extreme conditions and colonizing varied habitats and substrates, including the sulphide soils present in the region. However, the composition of the diversity of the fungi community present in these soils is still poorly understood. Within the Fungi kingdom, some species stand out for their ability to be acidophils, in addition to producing different organic acids of interest for application in biometallurgy, such as the metal bioleaching processes of industrial interest. Based on the above, this study aimed to characterize the diversity of cultivable fungi present in sulfide soils located on the Keller Peninsula, collected at 5 points on King George Island, Antarctica and to evaluate them for future studies of metal bioleaching. The sulfide soils were diluted to 10-2 and 100 μL of the dilution were inoculated in three media: Malt Extract-Yeast Extract (YM) with Chloramphenicol, medium rich in nutrients, Dichloran Glycerol Agar (DG18) Chloramphenicol, xerophilic medium and Dichloran Rose Bengal Chloramphenicol Base Agar (DRBC), selective medium for fungi, and incubated at 15 ° C for up to 60 days. After purification, the fungal colonies were grouped morphologically, and molecularly by amplification of the microsatellite regions, for further identification using molecular biology techniques. Eighty-five isolates in total, 74 filamentous fungi and 11 yeasts were obtained. Filamentous fungi were identified as belonging to 18 species. The most abundant were Mortierella amoeboidea, Mortierella globalpina, Mortierella turficola, Penicillium chrysogenum, Penicillium rubens. Yeasts were identified as Leucosporidium creatinivorum, Leucosporidium sp. and Rhodotorula mucilaginosa, the most abundant of which was L. creatinivorum. Growth tests were performed at different pH's (3.7, 9) and at different temperatures (5, 10, 15, 20, 25, 30, 35, 40 ° C). In the test of tolerance to different pH ranges, 76 fungi showed satisfactory growth at pHs 3, 7 and 9. Acid pH ranges are important in alkaline pH and bioleaching processes and are used in industrial chemical reaction steps, therefore, it is necessary to search for fungi that grow well at three different pH levels. All fungi were also evaluated for their ability to grow at different temperatures (5, 10, 15, 20, 25, 30, 35 ° C), which Hyaloscypha hepaticicola, M. amoeboidea, M. globalpina, M. turficola, P. chrysogenum and P. rubens grew in a wide temperature range from 5 to 35 35 ºC; L. creatinivorum, Leucosporidium sp.1, Leucosporidium sp.2, Leucosporidium sp.3, M. turficola, Pseudogymnoascus destructans, R.mucilaginosa and two unidentified yeast species grew well up to 25 ºC; and the species Leptobacillium leptobactrum, M.turficola, Pseudogymnoascus destructans and Antarctomyces psychrotrophicus that grew only in colder temperatures up to 20 ºC. The fungi H. hepaticicola, Leptobacillium leptobactrum, M. turficola, P.chrysogenum, P. rubens, Periconia prolifica, P. destructans, L. creatinivorum, Leucosporidium sp. and R. mucilaginosa were able to grow at pH 3 and also showed marked growth profiles for high temperatures up to 35 ºC and, therefore, considered promising for future studies of bioleaching of metals of interest, considering that acidic pH and mesophilic temperatures are commonly used in industrial processes. In the bioleaching test using a mining tailing complex, P. chrysogenum UFMGCB17938 biosorbed Strontium and Zinc, which are metals that can be removed for the processing of tailings, zinc being an important industrial anticorrosive and used in the manufacture of alloys and Strontium when associated with carbonated compounds, can be used to fix CO2 in the form of carbonates in mining concentrates. (Mr and Zn). Regarding the bioleaching of Iron and Manganese (metals more abundant in the tailings), despite not having reached high values, the results of the indices were significant for future optimization of the process. Iron and Manganese being important for the extractive industry, having great commercial value for steel industries. From the data sets obtained, acidophilic and mesophilic fungi present in the sulfide soils of Antarctica